Recepciones pragmatistas de Martin Heidegger - Federico Penelas, Federico (2011)
“Pragmatist Receptions of Martin Heidegger”. This paper studies theAmerican Pragmatist reception of Heidegger’s thought. The article briely presentsBrandom’s and Okrent’s readings of Heidegger, paying attention afterwards toRorty’s articulation of the Heideggerian legacy with the work of Wittgensteinand classical Pragmatists, especially Dewey. Rorty’s appropriation of Heideggerassumes a philosophical and metaphilosophical anti-essentialist commitment.This commitment requires some reading operations in relation to the lastHeidegger, who cannot be easily assimilated by the Pragmatist tradition. Thetension between irony and nostalgia will be crucial for Rorty’s appropriation ofHeidegger’s thought.